Subnational Capital Markets in Developing Countries : From Theory to Practice - Freire, Mila; Petersen, John; Huertas, Marcela; Valadez, Miguel (Washington, DC: World Bank and Oxford University Press, 2013)
In developing countries the twin tasks of building more dispersed and democratic governments and opening economies to freer markets and greater private ownership have been attempted in tandem-and have proved a difficult undertaking. A reduction in barriers to the movement of capital and goods has been a nearly universal objective. However, implementation of the required reforms has meant tough competition for domestic industries and increasing constraints on the fiscal and monetary policies of national governments. In the face of economic slowdowns and unstable financial markets, many emerging and developing economies have found privatization and the opening up of their economies to be painful and unpopular. The steep price and uncertain benefits of joining global markets have their critics. Subnational governments, for their part, are being required to do more things, to do them more efficiently, and to be more self-reliant in raising resources. At the same time devolution and hard-pressed budgets have constrained the ability of central governments to provide for the needs of subnational governments. After years of neglect and with expectations rising, the needs for infrastructure are particularly daunting. The enormous funding requirements cannot be met either practically or equitably without long-term investment. International lending and grant-giving institutions, another traditional source of funds, are also limited in their resources and restricted by rules and customary practice to dealing only through sovereign governments.